Analisis e-service quality pada aplikasi PeduliLindungi selama masa pandemi Covid-19 di DKI Jakarta - Laneisha Sherissa; Fikri Akbarsyah Anza (Universitas Merdeka Malang, 2022)
PeduliLindungi app is currently a mandatory app to do daily activities during COVID-19. The service quality of the PeduliLindungi app has become a public concern considering that the application is currently used by all people. However, users often have some trouble about PeduliLindungi app services, such as certificate of COVID-19 vaccine takes time to appear on the app, the registration procces usually had a trouble, and the response form PeduliLindungi team regarding the complaints of users tend to be long. Based from the previous problems, this thesis aims to analyse electronic service quality on PeduliLindungi app in DKI Jakarta. The approach used in this research is quantitative, with collection techniques is quantitative method through survey. Interviews and literature study used for supporting data. The results of this study indicate that e-service quality on PeduliLindungi app is in good category. That results proved by four dimensions of e-service quality proposed by Papadomichelaki dan Mentzas (2012), three dimensions are in good category and only one dimension is in bad category. Therefore, this study provides suggestions to Ministry of Health to develop some features and enrich information that makes it easier for users, and to the health center to set a deadline for inputting data on people who are vaccinated.